Perancangan Desain Packaging dalam Meningkatkan Daya Tarik pada Kedai Mie Esha - Dwi Fitriani; Ayyub Hamdanu Budi Nurmana MS; Muhammad Sholikhan (CV. ITTC INDONESIA, 2025)
aspects such as packaging as an effective marketing strategy. This study aims to redesign the packaging of Kedai Mie Esha to make it more attractive, informative, and reflective of a consistent brand identity. The research employs a Research and Development (R&D) method with a qualitative approach, encompassing observation, interviews, SWOT analysis, design, validation, revision, and product testing. Data were collected through direct interaction with the owner and field observation. Findings reveal that the previous styrofoam packaging lacked visual appeal and brand identity. The redesigned packaging, made from ivory paper and polypropylene for beverages, integrates visual elements such as the logo, warm color tones, bold typography, and business contact information. The final design enhances visual appeal, strengthens brand image, and improves promotional effectiveness across both offline and online platforms. The study implies that integrating aesthetic and functional elements in packaging design plays a crucial role in increasing product value and expanding market reach, especially for local culinary businesses.